2002
DOI: 10.1074/jbc.m203020200
|View full text |Cite
|
Sign up to set email alerts
|

A Novel p53 Transcriptional Repressor Element (p53TRE) and the Asymmetrical Contribution of Two p53 Binding Sites Modulate the Response of the Placental Transforming Growth Factor-β Promoter to p53

Abstract: Previous studies in our laboratory and others identified placental transforming growth factor-␤ (PTGF-␤) as an important downstream mediator of DNA damage signaling and a transcriptional target of p53. Here we show that accumulation of PTGF-␤ mRNA in response to p53 overexpression is delayed relative to p21 WAF1 , whereas the promoters of these genes respond to p53 with similar kinetics. Mutational analyses of two p53 binding sites within the PTGF-␤ promoter revealed that site p53-1 (؉29 bp) is responsible for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
17
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Moreover, neither p53 nor hPitx1 were able to transactivate the PTGFb gene promoter with both the p53-responsive sites mutated, consistent with previous observations that mutation of both sites completely abolished p53 responsiveness. 29 Similar results were obtained for p21, for which hPitx1 was shown to indirectly transactivate the p21 promoter via p53 activation (Figure 8b). …”
supporting
confidence: 72%
See 1 more Smart Citation
“…Moreover, neither p53 nor hPitx1 were able to transactivate the PTGFb gene promoter with both the p53-responsive sites mutated, consistent with previous observations that mutation of both sites completely abolished p53 responsiveness. 29 Similar results were obtained for p21, for which hPitx1 was shown to indirectly transactivate the p21 promoter via p53 activation (Figure 8b). …”
supporting
confidence: 72%
“…11 A multitude of p53 target genes have been implicated in this process. 7 Among them, PTGFb 29 and cyclin-dependent kinase inhibitor p21 7,14 are two well-known direct transcriptional targets of p53. To determine whether hPitx1 was able to activate the expression of these two p53 downstream target genes via p53 activation, a luciferase reporter plasmid containing wildtype PTGFb promoter, which possesses two functional p53-responsive elements, was co-transfected into MCF-7 cells with plasmids expressing hPitx1 and its dominant-negative mutant hPitx1-R141P, wild-type p53 and its dominantnegative mutant p53-143A, and/or HPV-E6, the human papilloma virus type-16 E6 oncoprotein that promotes the degradation of p53 through its interaction with the P-labeled probes.…”
mentioning
confidence: 99%
“…9 The promoter of GDF-15 contains two distinct p53-binding sites with different binding affinity to p53 in vitro. Interestingly, Wong et al 51 identified a novel p53 transcriptional repressor element in close proximity of the p53-binding sites, suggesting a complex regulation of activation of GDF-15 in a manner dependent on cell or signaling context. GDF-15 represents a typical gene of the adaptive response to cellular stress, as its expression is generally low in quiescent cells, but is rapidly enhanced by different stress stimuli that employ different signaling pathways.…”
Section: Regulation Of Gdf-15 Expressionmentioning
confidence: 99%
“…According to in vitro experiments, the p53 protein binds specifically to a palindromic consensus sequence, RRRCWWGYYY(N 0À13 )RRRCWWGYYY [15], with nearly all REs containing at least one mismatch; in vivo results have suggested that the spacer region may be much smaller [14,15]. The sequence is typically located within 5,000 bases of the target gene's transcriptional start site, and p53 either induces or represses expression upon p53 binding [16,17]. One feature of p53 that confounds the discovery of novel transregulated genes is that while some binding sites match the expected consensus sequence quite well, others can be consensus poor and yet are both necessary, and sufficient, to transactivate a gene [18].…”
Section: Introductionmentioning
confidence: 99%